MoS2 quantum dots decorated reduced graphene oxide as a sulfur host for advanced lithium-sulfur batteries. (10th December 2019) - Wei, Hao; Ding, Yusen; Li, Hong; Zhang, Qin; Hu, Nantao; Wei, Liangming; Yang, Zhi
Abstract: Lithium-sulfur batteries have been considered as one of the most promising candidate for replacing Li-ion batteries because of its extremely high energy density and theoretical specific capacity of sulfur cathode. However, the "shuttle effect" caused by soluble long-chain lithium polysulfides (LiPS) has impeded further development of Li–S batteries. In this work, nanosized MoS2 quantum dots (MoS2 QDs) were decorated on three-dimensional (3D) structure of reduced graphene oxide (rGO) to form aerogels for sulfur host, in which the MoS2 QDs provide much more unsaturated bonds to enhance chemical absorption with LiPS and rGO acts as an electron transfer pathway as well as physical absorption with LiPS. Impressively, the rGO-MoS2 QDs/S electrodes have reached an ultra-low capacity fade rate of 0.011% per cycle during 300 cycles at 2 C with an average coulomic efficiency of nearly 100%. We believe that our reasonably designed unique nanostructure can reveal its potential for high performance of Li–S batteries. Graphical abstract: Image 1 Highlights: First report MoS2 quantum dots (MoS2 QDs) used in Li–S batteries. The quantum dots were in situ decorated on 3D structure of rGO to form aerogels. The electrodes reached the fade rate of 0.011% per cycle at 2 C during 300 cycles.